Planning and development of a treatment introducing Logotherapy and Psychoanalytic Psychotherapy - Ovejas, Patricia (2013)
In this study, it is intended to demonstrate the possibility and importance of the Logotherapy and Psychoanalytic Psychotherapy integration, since a clinical case. The case was selected from among several who are in treatment at the “Orientación María Madre del Pueblo” Center of the Town 1-11-14 (one of the most emergency settlement population density of Argentina), in the same it is carry out a care activity guided through the theoretical framework proposed inthis study. Within a focal treatment, semi-structured interviews were made and Logotherapeutic technique was administrated, this technique is called “autobiography”. As a result, there was a favorable evolution of the patient, with the development of resilient attitudes and the development of traumatic experiences.